Electromechanics modelling of the effects of myocardial infarction on left ventricular remodelling / Leong Chin Neng - Leong , Chin Neng (2020)
Myocardial infarction (MI) is one of the diseases with the highest mortality rate. Following MI, myocardium experiences abrupt changes in its loading condition due to the presence of infarct. In response to such changes, myocytes undergo adaptations to maintain homeostasis. However, maladaptation can happen and lead to remodelling, in which the left ventricle (LV) gradually loses its function and eventually turns into heart failure. Nevertheless, the mechanisms underlying LV remodelling are still poorly understood. In this study, a generic LV model was developed, incorporating realistic fibre orientation and excitable contracting myocardium. It was demonstrated that the developed model is capable of reproducing physiological LV functions, including action potential propagation, LV pressure and cavity volume, LV twisting and wall thickening. Subsequently, the generic LV model was utilised to investigate the effects of the infarct state on LV regional mechanics, including the interaction between non-contractile infarct and contractile myocardium. It was found that infarct transmural extent (TME) is more important than infarct size in determining LV regional mechanics impairments. Neighbouring contractile myocardium and non-contractile infarct induce a mechanical tethering effect, which elevates with infarct TME, at the border zone (BZ). Such mechanical tethering causes the BZ to have high systolic fibre stress, elevated energy expenditure and reduced myocardial energy efficiency, which are believed to give rise to infarct extension. The generic LV model was then modified into a patient-specific model, incorporating patient-specific infarcted LV geometry and optimised regional material properties, to study the correlation between infarct extension and myocardial mechanics impairments, including the underlying mechanisms responsible for the impairments. Among the observed myocardial mechanics impairments, only the depressed myocardial energy efficiency was found to be correlated with infarct extension. The depressed myocardial energy efficiency was due to inadequate generation of contraction force, which, at least in part, owing to inadequate stretching of myocardium at end-diastole (the Frank-Starling law). Although a stiff infarct can prevent infarct expansion, results of this study showed that it can also cause the neighbouring myocardium to be under stretched at end-diastole, thereby depressing the generated contraction force and energy efficiency during systole, which were found to be correlated with infarct extension of the neighbouring myocardium.